PENGARUH MODEL PEMBELAJARAN KOOPERATIFTIPE THINK-TALK-WRITE TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS PESERTA DIDIK KELAS IX SMP 25 PADANG - Ababil, Zahra; Suherman, Suherman (Jurnal Edukasi dan Penelitian Matematika, 2024)
Mathematical creative thinking ability is an ability to think of students who produce new and unique ideas, ideas and concepts to solve a mathematical problem. But in its implementation, this ability is still relatively low in class IX students of SMP Negeri 25 Padang. One of the solutions given is to use the Think Talk Write (TTW) cooperative learning model. The purpose of the research is to analyze and find out whether the ability of students who learn using this learning model is better than the Direct learning model and determine the development of the ability of students who learn using the Think Talk Write type cooperative learning model. This research is classified as a quasy experiment category with a research design of nonequivalent post-test only control group design. The data on the development of these abilities is described based on the quiz results, while the test results are analyzed using the ?-test, obtained ?-????? = 0.001 so reject H0. Based on the quiz results, it was found that the development of their abilities increased, and based on the results of the test analysis, it was found that the ability of students who learned using the Think Talk Write type cooperative learning model was better than the Direct learning model in class IX SMP Negeri 25 Padang.Keywords– Cooperative Learning type Think Talk Write, Direct Learning, Mathematical creative    thinking ability